A water-stable metal–organic framework of a zwitterionic carboxylate with dysprosium: a sensing platform for Ebolavirus RNA sequences. Issue 1 (27th October 2015) - Qin, Liang; Lin, Li-Xian; Fang, Zhi-Ping; Yang, Shui-Ping; Qiu, Gui-Hua; Chen, Jin-Xiang; Chen, Wen-Hua
Abstract : A 3D Dy-based metal–organic framework (MOF)1 was synthesized. Compound1 can interact with the probe DNA to form a P-DNA@1 system. This system can be used as an effective fluorescent sensing platform for the detection of Ebolavirus RNA. Abstract : We herein report a water-stable 3D dysprosium-based metal–organic framework (MOF) that can non-covalently interact with probe ss-DNA. The formed system can serve as an effective fluorescence sensing platform for the detection of complementary Ebolavirus RNA sequences with the detection limit of 160 pM.